Women in the National Academy of Medicine of Venezuela Recent advances towards gender equality, Goal 5 of the UN 2030 Agenda for Sustainable Development - Cruz, Dra. Lilia (Gaceta Médica de Caracas, 2020)
To assess how the Venezuelan National Academy of Medicine (NAM) is progressing on gender equality, established as Goal 5 of the United Nations (UN) 2030 Sustainable Development Agenda, a quantitative analysis of the process of incorporating women to the institution and its governing board is presented. Para conocer cómo la Academia Nacional de Medicina de Venezuela (ANM) avanza para lograr la igualdad de género entre sus miembros, establecida como meta No 5 en la Agenda 2030 de la Organización de las Naciones Unidas (ONU) para el Desarrollo Sostenible, realizamos un análisis cuantitativo del proceso de incorporación de la mujer a la institución y a sus órganos de dirección.